Effects of extraction methods on the structural characteristics and functional properties of dietary fiber extracted from kiwifruit (Actinidia deliciosa). (January 2021) - Wang, Kunli; Li, Mo; Wang, Yuxiao; Liu, Zihao; Ni, Yuanying
Abstract: The methods of enzymatic extraction (EE), acid extraction (ACE), and alkali extraction (ALE) were applied for extracting the soluble and insoluble dietary fiber (SDF and IDF) based on the kiwifruits. The scanning electron microscopy (SEM), molecular weight, Fourier transform infrared spectroscopy (FT-IR), monosaccharide composition, and thermal properties were adopted for characterizing dietary fiber samples. This study demonstrated that, all the dietary fiber samples showed representative infrared spectral features of polysaccharides (LPS), whereas AC-IDF and E-SDF had the looser and more complicated structures. AL-IDF displayed greater thermal stability among IDFs, and there was no significant difference in the thermal stability of SDFs. Both AC-IDF and AC-SDF had higher molecular weights among the various IDFs and SDFs. In addition, the extraction method indeed had certain effect on the monosaccharide composition in dietary fiber samples. Furthermore, E-SDF, E-IDF, AC-SDF and AC-IDF exhibited higher glucose adsorption capacity (GAC), oil-holding capacity (OHC), water-holding capacity (WHC), bile acid binding capacity (BABC), and nitrite ion adsorption capacity (NIAC) than those of AL-SDF and AL-IDF. To sum up, our results indicate that, the kiwifruit-derived dietary fiber samples may potentially serve as the functional food ingredient. Graphical abstract: Image 1 Highlights: ALE had the highest TDF and SDF yields. DFs showed representative FT-IR features of polysaccharides, while AC-IDF and E-SDF had more complex and loose structures. E-DF and AC-DF exhibited superior functional properties to AL-DF. Extraction method had certain effect on structural and functional characteristics of SDF and IDF extracted from kiwifruits.